2020
DOI: 10.1590/2175-7860202071097
|View full text |Cite
|
Sign up to set email alerts
|

Montane seasonal wetlands: an inventory of its associated flora in Parque Estadual do Ibitipoca, southeast Brazil

Abstract: The aim of the present study was to perform the floristic survey of the wetlands of the Parque Estadual do Ibitipoca (PEIB), comparing them regarding richness, floristic composition and life forms, based on monthly expeditions to collect vascular plants. Eighty-one (81) species were found in the moist grassland, most of them being endemic to Brazil and included in 55 genera and 21 families. The most representative families were Asteraceae (22 spp.), Melastomataceae (nine spp.), Xyridaceae (seven spp.), Poaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Through this investigation, it was possible to deduce the relationships between species' ecological characteristics and their growing environment. There is a lack of research on this problem in wetlands, even though it is generally accepted that ecological development conditions affect species richness through decreased nutrient availability and slower rates of nitrogen mineralization and nitrification (Rajilesh et al, 2016;Cruz et al, 2020). The relevance of water composition and lighting conditions for their maintenance was highlighted by the current study, which showed a correlation between practically all ecogroups of macrophytes and the ecological parameters of locales.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 53%
“…Through this investigation, it was possible to deduce the relationships between species' ecological characteristics and their growing environment. There is a lack of research on this problem in wetlands, even though it is generally accepted that ecological development conditions affect species richness through decreased nutrient availability and slower rates of nitrogen mineralization and nitrification (Rajilesh et al, 2016;Cruz et al, 2020). The relevance of water composition and lighting conditions for their maintenance was highlighted by the current study, which showed a correlation between practically all ecogroups of macrophytes and the ecological parameters of locales.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 53%